Design of Nanoporous Carbons as Anode Materials for Sodium (Na) Ion Batteries. (2nd August 2016) - Karatrantos, Argyrios; Cai, Qiong
Abstract : Molecular dynamics simulations have been employed to study the structural properties of non-aqueous (organic) electrolyte solutions confined within carbon nanopores. The effects of pore size and surface charge density were quantified by calculating ionic density profiles and concentration within the pores. Graphene slit pores of widths 0.72-10 nm were considered. The graphene surfaces were charged with densities ranging from 0 (neutral pores), -0.8e/nm 2, -1.2e/nm 2, -2e/nm 2 . As the surface charge density increases, more Na + ions enter the pores. When the graphene surface is highly charged the Na + ions are adsorbed due to counterion condensation effect.